The gut-muscle axis: a comprehensive review of the interplay between physical activity and gut microbiota in the prevention and treatment of muscle wasting disorders - Xu, Yan; He, Benxiang (Frontiers in Microbiology, 2025)
Skeletal muscle wasting disorders, such as sarcopenia and cachexia, pose a significant clinical challenge. The gut-muscle axis, a bidirectional signaling network, is now understood to be a critical regulator of muscle homeostasis, with the gut microbiota functioning as a key metabolic organ. Physical activity is a cornerstone intervention, exerting benefits by directly stimulating muscle and by favorably modulating the composition and metabolic output of the gut microbiota. This review synthesizes the molecular mechanisms of muscle wasting and the pathways of the gut-muscle axis, with a specific focus on microbial metabolites like short-chain fatty acids (SCFAs). We analyze how different exercise modalities modulate this system and critically evaluate evidence from human trials. By identifying key research gaps, this review argues for a paradigm shift toward integrated, personalized interventions that combine targeted exercise with nutritional and microbial strategies to more effectively combat muscle wasting disorders.